Graffiti of Healing: Therapeutic Elements of Hip-Hop Dance among Indian Youth - Tanushree Mishra; Oindrila Mukherjee (Creative Arts in Education and Therapy)
What started in the 1970s as a mark of protest and revolution, hip-hop dance, with its various sub-categories, has grown over the years and has spread throughout the world prominently among the youth. This greater affinity toward this street art form has captured the attention of multiple western researchers on identity formation, self-expression, emotional regulation, and resilience. However, similar research studies remain scarce in the Indian context despite the growing affinity of the youth, especially the ones on the margins, toward this street form. Thus, this study aimed to understand the potential therapeutic elements in hip-hop dance reaped by the Indian youth in the age range of 19 to 29 years through a qualitative approach with interviews as the mode of data collection. With themes of “selfhood,” “impact on mental health,” “presence of community,” “resilience building” and “mind-body nexus,” the primary finding was of the strengthened attunement of the mind and body that favorably impact other domains of their life. Further research could explore the implications and applicability of the results in the therapeutic settings in the Indian context.